Reconsidering Eusebius : collected papers on literary, historical, and theological issues - Inowlocki, S.; Zamagni, Claudio. (Vigiliae Christianae, Supplements, 2011)
Over the last decades, Eusebius has been the focus of a great deal of attention. New light has been shed both on his writings and on his personality, which has led to a welcome re-assessment of his significance. As a result, he is no longer perceived as a mere compiler but as a powerful author who largely contributed to the construction of the orthodox Church's triumphalism. This volume seeks to contribute to the ongoing re-evaluation of Eusebius as an active participant to the construction of late antique history, theology, and literature. The result is an interdisciplinary collection of articles by an international team of scholars who offer innovative papers on one of the most important late antique author.